Weapons and the law of armed conflict - Boothby, William H. (Oxford : Oxford University Press, 2009)
This is an examination of the international law of armed conflict as it applies to weapons. The text interprets the rules governing the use of weapons and discusses the factors influencing developments in the law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Military weapons -- Law and legislation; Nuclear weapons (International law); War (International law); Humanitarian law